Ultrastructure Analysis and Molecular Characterization of Trichomitus batrachorum (Parabasalia; Hypotrichomonadida) Isolated from Liver of Ameiva ameiva (Reptilia: Squamata) - Lina Maria Pelaez Cortes; Júlia de Castro Ascenção; Rhagner Bonono dos Reis; Gabriela Peixoto; Gabriel Gazzoni Araújo Gonçalves; Jana Messias Sandes; Fábio André Brayner dos Santos; Luiz Carlos Alves; Felipe Arley Costa Pessoa; Claudia María Ríos Velásquez; Helena Lúcia Carneiro Santos (Microorganisms, 2025)
Trichomitus batrachorum is a species of trichomonad that has gained attention due to its ecological importance and potential interactions with various hosts, such as amphibians (anurans) and reptiles (lizards and chelonians), where it has been recorded in the gastrointestinal tract of these vertebrates, specifically in their feces. Molecular studies have placed this flagellated protist within the Metamonada clade. Unlike parabasalids that inhabit endothermic mammals in relatively stable temperature conditions, protists associated with ectothermic reptiles are subject to significant temperature fluctuations. The ability of T. batrachorum to thrive in the variable temperatures encountered by reptiles suggests that its parasitism may remain largely unaffected by climate change. In our study, we detected and characterized T. batrachorum from the liver tissue of the lizard species Ameiva ameiva, collected in Presidente Figueiredo Municipality, Amazonas State, Brazil. The identification of T. batrachorum was confirmed by cultivation technique, light microscopy, scanning electron microscopy and transmission electron microscopy for ultrastructural analyses, and sequencing the 5.8S rDNA (region ITS1- ITS2) and 18S rRNA (ribosomal RNA) genes. One potential interpretation for this finding is that the flagellates may have migrated from the intestine to the bile duct, ultimately reaching the liver. This is the first successful characterization of T. batrachorum in the liver of a lizard, and provides a solid foundation for further research to elucidate the potential pathogenicity of this flagellate and the role of A. ameiva in the epidemiology of parabasalids in other animal species.